2021
DOI: 10.1128/msystems.00188-21
|View full text |Cite
|
Sign up to set email alerts
|

Representative Diatom and Coccolithophore Species Exhibit Divergent Responses throughout Simulated Upwelling Cycles

Abstract: Wind-driven upwelling followed by relaxation results in cycles of cold nutrient-rich water fueling intense phytoplankton blooms followed by nutrient depletion, bloom decline, and sinking of cells. Surviving cells at depth can then be vertically transported back to the surface with upwelled waters to seed another bloom. As a result of these cycles, phytoplankton communities in upwelling regions are transported through a wide range of light and nutrient conditions. Diatoms appear to be well suited for these cycl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 87 publications
(164 reference statements)
1
11
0
Order By: Relevance
“…It remains to be determined what roles plastidial glycolysis plays in other habitats where diatoms dominate phytoplankton biomass, e.g. in upwelling cycles where diatoms may preciously upregulate components of their core metabolism to rapidly avail of optimal light and nutrient conditions (119, 122)…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined what roles plastidial glycolysis plays in other habitats where diatoms dominate phytoplankton biomass, e.g. in upwelling cycles where diatoms may preciously upregulate components of their core metabolism to rapidly avail of optimal light and nutrient conditions (119, 122)…”
Section: Discussionmentioning
confidence: 99%
“…Upwelling-simulation studies conducted in the laboratory have recently showed an increase in the relative expression of nitrogen assimilation genes in the dark (simulated sinking out of the euphotic zone) in the diatom Chaetoceros decipiens , while the coccolithophore, Emiliania huxleyi showed a relatively lower expression of the same genes in the dark, further supporting the diatom “frontloading” hypothesis for N assimilation [Lampe et al 2021]. Ultimately, diatoms can ensure a more rapid physiological response to upwelling compared to other phytoplankton taxa.…”
Section: Introductionmentioning
confidence: 85%
“…In essence, upwelled diatoms employ a proactive approach and maintain elevated pools of these nitrogen-related genes throughout the upwelling conveyor belt cycle, whereas other phytoplankton employ a more reactive approach and upregulate primary nitrate assimilation genes post-upwelling. This distinctive molecular strategy to constitutively express nitrogen assimilation genes is believed to provide these diatom taxa with a physiological edge in their "shift-up" response to upwelling [Lampe et al 2021].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations